Decision-making for people with dementia and advanced kidney disease: a secondary qualitative analysis of interviews from the Conservative Kidney Management Assessment of Practice Patterns Study. Issue 11 (12th November 2018) - Scott, Jemima; Owen-Smith, Amanda; Tonkin-Crine, Sarah; Rayner, Hugh; Roderick, Paul; Okamoto, Ikumi; Leydon, Geraldine; Caskey, Fergus; Methven, Shona
Abstract : Objective: To explore dialysis decision-making for adults who lack capacity due to cognitive impairment, a common and under-recognised condition in those with advanced chronic kidney disease (CKD). Design: Secondary analysis of qualitative data collected during the Conservative Kidney Management Assessment of Practice Patterns Study programme of research was performed. Sixty semistructured interviews were conducted with multiprofessional team members from UK renal centres. Staff were asked about local facilities, the value of conservative kidney management (CKM), when and with whom CKM was discussed and how CKM could be improved. Thematic analysis was employed to identify, characterise and report on themes that emerged from the data, focused on the specific issues experienced by people with dementia. Setting: A purposive sample of nine UK renal centres differing in the scale of their CKM programmes. Participants: Clinical directors of renal centres identified staff involved in CKM. Staff were asked to participate if they had experience of low clearance clinics or of caring for patients with advanced CKD (estimated glomerular filtration rate <20mL/min/1.73 2 or >65 years with end-stage kidney disease). Results: Two overarching themes were identified: factors taken into consideration during decision-making, and the process of decision-making itself. Comorbidity, social support, quality of life and the feasibility of dialysis were reported as factors pertinent to clinicians' decisions regarding suitability. The majority of renal centres practised multidisciplinary 'best interests' decision-making for those without capacity. Attitudes to advance care planning were divided. Conclusions: In view of the prevalence of cognitive impairment among those with advanced CKD, we suggest consideration of routine assessment of cognition and capacity. In the UK, dialysis is initiated and continued for individuals with dementia and services should be adapted to meet the needs of this population.